Investigations of nonlinear dynamic performance of top-and-seat with web angle connections subjected to sudden column removal. (15th September 2015) - Liu, Chang; Tan, Kang Hai; Fung, Tat Ching
Highlights: Dynamic responses were observed for top-and-seat with web angle (TSWA) connection under sudden column loss. 3D numerical models were validated by comparing with static and dynamic test results. Full dynamic responses of the TSWA connection were investigated. A DIF of 2.2 is suggested for the connections to resist progressive collapse. Abstract: It is well known that progressive collapse is a complicated dynamic process with geometry and material nonlinearities. Sudden column removal scenario is a simple yet effective method for analysis and design of structures to mitigate progressive collapse. The main objective of this study is to investigate the dynamic performance of top-and-seat with web angle (TSWA) steel beam–column connections under progressive collapse condition. This type of connection represents typical bolted cleat connections with excellent ductility. Each specimen consisted of two adjoining beams pinned at the far ends and connected to a middle column stub. Five dynamic tests for the TSWA connections subjected to sudden removal of the middle columns were conducted in Nanyang Technological University. Another five corresponding static tests were also carried out for comparison with the dynamic behaviour. Test results showed that the release-time durations of the column support force were around 30 ms for all the five dynamic tests. Transient dynamic responses with free vibrations were observed for the connections following instantaneous removal of the middle columns. The maximum dynamic displacement was significantly increased compared to the static connection response. In addition, numerical simulations were also conducted using the general-purpose finite element software ABAQUS. The three-dimensional finite element model was validated by comparing the simulation results against the test data. Parametric studies were carried out to investigate the full dynamic connection performance and its structural resistance under push-down analysis to simulate progressive collapse. By comparing the full dynamic response with its corresponding quasi-static response, both the displacement-based dynamic increase factor (DIF) and force-based DIF were investigated, respectively. The paper ends with some discussions on practical applications of displacement-based DIF and force-based DIF.